Javanese Cultural Dynamics and the Halal Industry: A Systematic Literature Review - Wimpow Panjaitan; Heru Kurnianto Tjahyono; Claudius Budi Santoso (LP2M IAIN Palopo, 2025)
The interaction of culture, particularly Javanese culture, with the halal industry is a unique topic, as it examines how long-held traditional values adapt to modern developments within the halal industry, which has an Islamic identity. More comprehensive research is needed, gathering perspectives from relevant literature related to Javanese culture and the halal industry. Therefore, this study aims to gather various literature and its developments, while analyzing them to identify key themes, identify research gaps, and provide possible future research directions. The Systematic Literature Review (SLR) method, using the PRISMA program using the Watase UAKE program, was chosen to achieve the research objectives. The research results demonstrated the relevance and validity of 47 articles out of 142 Scopus articles. The publication trend for